2001
DOI: 10.1080/09637480020027000-8
|View full text |Cite
|
Sign up to set email alerts
|

The association between nutrition knowledge and eating behavior in male and female adolescents in the US

Abstract: Some factors that could influence adolescent eating behavior include: peer influences, nutrition knowledge and beliefs, mass media, and parental dietary habits. The purpose of this study was to examine the correlation of nutrition knowledge and eating behavior of a sample of middle school children. The participants were 532 students in the sixth, seventh, and eighth grades between the ages of 11 and 13 from Shawnee Middle School in Lima, Ohio. The students were asked to answer a questionnaire, CANKAP (Comprehe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
73
0
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(92 citation statements)
references
References 10 publications
15
73
0
4
Order By: Relevance
“…Girls approaching adolescence may become more concerned with their appearance, losing weight, and being thin. This finding is in line with Pirouznia (2001) and Xie and colleagues' (2003) finding that girls ate fewer unhealthy foods than boys as they grew older. Pre-adolescent girls receive a barrage of messages about body size, shape, and weight.…”
Section: How Do Children's Eating Behaviors Differ By Grade and Gender?supporting
confidence: 93%
See 2 more Smart Citations
“…Girls approaching adolescence may become more concerned with their appearance, losing weight, and being thin. This finding is in line with Pirouznia (2001) and Xie and colleagues' (2003) finding that girls ate fewer unhealthy foods than boys as they grew older. Pre-adolescent girls receive a barrage of messages about body size, shape, and weight.…”
Section: How Do Children's Eating Behaviors Differ By Grade and Gender?supporting
confidence: 93%
“…In contrast, only 85% of eighth-grader students consumed breakfast: similarly, eighth-grader students' fruit intake fell to 41% and vegetable intake fell to 25% (Lytle et al, 2000). Pirouznia (2001) found similar results in a sample of 532 middle school students. Nutrition knowledge and eating behaviors were poorer in older students.…”
Section: Gender Grade and Ethnicitysupporting
confidence: 68%
See 1 more Smart Citation
“…These results can be explained by the fact that girls have more knowledge on nutritional (Pirouznia 2001) awareness and also make diets for loss of weight more often than and consequently consuming more fruits and vegetables (Yannakoulia et al 2004). …”
Section: Discussionmentioning
confidence: 98%
“…The influence of nutrition knowledge on food behavior has no consensus (Taylor et al 2005): Some studies found a weak association or no correlation at all (Mullaney, Corish, and Loxley 2009;Pirouznia 2001;SerraMajem et al 2007); others found a significant positive association (De Vriendt et al 2009;Shah et al 2010;Sharma, Gernand, and Day 2008), or a positive association only with fruits and vegetables (De Vriendt et al 2009;Parmer et al 2009;Wardle, Parmenter, and Waller 2000) or fat consumption .…”
mentioning
confidence: 96%